ANALISIS PENGARUH KESADARAN MERK, PERSEPSI KUALITAS, DAN ASOSIASI MERK TERHADAP LOYALITAS PELANGGAN SABUN CUCI MERK SO KLIN - Pramudewa, Dian Gamma; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2015)
The research was conducted regarding to the stagnant condition of brand value survey result of So Klin detergent product for three years continually. Accordingly it is necessary to find out what factors might interfere the loyalty of the consumer of So Klin product. This study aims to determine the effect of brand-awareness, quality perception, and brand association, to consumer loyalty of So Klin detergent product. The research data was collected from 112 consumers of So Klin detergent in Gayamsari Semarang district. Sampling in this study is using the accidental sampling technique. The analysis used in this study is multiple regression analysis. Previously it was deal with validity and reliability testing and classical assumption testing. Afterwards it was provided by the hypothesis testing and coefficient of determination. Considering to data analyzed, the regression equation is summarized as follows: Y = 0,269X1 + 0,060 X2 + 0,469 X3 + e . Regression analysis showed variable of brand-awareness, brand association and quality perception have a positive influence to the consumer loyalty. The most influential variable was the brand association as 0.469, consider brand-awareness as 0.269. Yet the quality perception has the least influence as 0.060. The analysis result using t test showed that the brand-awareness, the brand association have individually influence to the significant consumer loyalty. The equation model had F value of 27.941 with a significance level as 0,000. The analysis result using the determination coefficient was leveled about 41.9%. The consumer loyalty indicated by the variable of brand-awareness, quality perception, and brand association, whilst 58.1% summarized by other variable which unstated in this research.